Effect of Two Different Volumes of Ropivacaine and Lignocaine at Two Different Sites in Ultrasound-Guided Supraclavicular Brachial Plexus Block on Diaphragm Motility - Prasad, Jagat Narayan; Uprety, Prashanta; Khatiwada, Sindhu; Ghimire, Ashish; Guddy, Km; Sarraf, Deependra Prasad (Nepal Medical College Journal, 2022)
Ultrasound (USG) guided supraclavicular brachial plexus block (BPB) helps in precise delivery of local anesthetic injection, reduced volume or dose of drug providing excellent surgical anesthesia with fewer complications. Objective of the study was to compare effect of two different volumes of Ropivacaine and Lignocaine at two different sites of USG-guided supraclavicular BPB on diaphragmatic motility, quality of block and tourniquet pain. A prospective randomized double-blinded comparative study was conducted among adult patient with below elbow elective surgery. In group A patients (n=17), 20ml of anesthetic solution was injected in the corner pocket and 10ml in the nerve cluster guided with USG. In group B patients (n=17), 15ml of the anesthetic solution was injected in the corner pocket and 5ml in the nerve cluster guided with USG. Hemodynamic parameters, diaphragmatic excursion, onset of anesthetic effects were measured at frequent intervals. The data were analyzed using Statistical Package for Social Sciences at P-value less than 0.05. Hemodynamic profile of the patients were similar in both groups (P-value>0.05). Statistically significant hemi-diaphragmatic dysfunction (partial and complete paralysis) after 15 and 30minutes of blockade was more common in group A than Group B (P<0.05). At 30 minutes after the injection of the anesthesia, all patient in both the groups had complete sensory and motor block in all nerve territory. Tourniquet time was lower in group A (80.35±9.59 minutes vs 84.12±7.75 minutes); however, it was statistically not significant (P-value>0.05). The present study showed that the patients who received lesser half of the required volume of local anesthetics had less incidence of hemidiaphragmatic dysfunction with similar successful rate of blockage (100%) and similar quality of the block as compared to the patients who received greater half of the required volume of local anesthetics.